Classification of Tourism Villages in Sleman Regency in 2022: Quantitative and Qualitative Analysis Based on Sustainable Tourism Indicators - Al Anshori, Hannif Andy; Dzulkifli, Muhammad (Ann Publisher, 2025)
Background. Tourism villages are a model for community-based tourism development that plays a vital role in improving economic welfare, cultural preservation, and maintaining environmental sustainability. Sleman Regency, as one of the centers of tourism growth in the Special Region of Yogyakarta, has experienced a significant increase in the number of tourist villages in the last five years. Purpose. This study aims to map the status of tourism village development in Sleman Regency in 2022 and analyze strengths, weaknesses, opportunities, and challenges based on ten leading indicators: institutional human resources, partnerships, environmental and cultural preservation, community roles, tourist attractions, accessibility, amenities, promotion and marketing, disaster mitigation, and CHSE. Method. The research uses quantitative and qualitative approaches through observation, in-depth interviews, documentation, and assessment instruments based on the ASEAN CBT Standard, the 2019 Tourism Village Guidelines, and UNWTO sustainability indicators. Results. The results of the study show that 80 active tourism villages out of a total of 85 registered tourism villages, with the composition of pioneers (39%), developing (21%), advanced (20%), and independent (14%). Qualitative findings confirm the weak aspects of partnerships, disaster mitigation, and digital marketing in start-up and developing villages. Conclusion. Independent tourism villages have optimized USP, industrial partnerships, and institutional strengthening. Implementation. This study recommends a category-based development strategy to increase the competitiveness of tourism villages in a sustainable manner.